Linfangioma cervical digante en pediatría: A propósito de un caso grave - Luna Muñoz, Consuelo del Rocio (2026)
Lymphatic malformations (LM), such as giant cervical lymphangioma, are benign head and neck anomalies in childhood that are susceptible to serious complications such as superinfection. We present the case of a 3-year-old girl with a small right cervical mass since birth, which suddenly increased in size with pain, fever, and signs of inflammation. Examination revealed a soft, painful mass measuring 10 x 8 cm. CT confirmed a giant multicystic lesion (10.7 x 9.5 x 8.4 cm) in the right cervical region, displacing vital structures. The diagnosis was superinfected giant cervical lymphangioma. It was initially treated with antibiotics. Subsequently, complete surgical resection of the tumor (11.5 x 9 x 6 cm) was performed, preserving adjacent structures. Histopathology confirmed the diagnosis. The patient was discharged with a favorable outcome. The case highlights the need for timely evaluation and multidisciplinary management to treat acute exacerbations and ensure a positive prognosis.